Essentials of Robotic Surgery - Kroh, Matthew; Chalikonda, Sricharan (Springer International Publishing : Imprint: Springer, 2015)
Essentials of Robotic Surgery is designed to present a comprehensive and state-of-the-art approach to robotic surgery within the broad confines of general surgery. Sections address preliminary issues surgeons face when initially undertaking robotics. These areas include training, basic techniques, setup, and general troubleshooting. Subsequent chapters focus on specific disease processes and the robotic applications for those procedures. Written by experts in the field, each of these sections address patient selection, preoperative considerations, technical conduct of the most common operations, and avoiding complications. A brief review of the existing literature addressing the particular topic follows in each section. The text concludes with chapters on other robotic platforms beyond the only current FDA approved device (Intuitive Surgical) as well as future directions, including single-site, enhanced imaging, 3-D modeling, and tele-proctoring, including to and distant site surgery. Extensive illustrations and links to video make this an interactive text.   Essentials of Robotic Surgery is of great value to general surgeons and associated sub-specialists, trainees including residents and fellows, fully trained surgeons looking to start a robotic surgery practice, and experienced robotic surgeons looking to expand the types of procedures that they currently perform robotically.